COST BENEFIT ANALYSIS IN MALAYSIAN EDUCATION - Husaina Banu Kenayathulla (Prodi Manajemen Pendidikan Jurusan Administrasi Pendidikan Fakultas Ilmu Pendidikan UNY, 2010)
Abstract An accurate, in-depth cost benefit analysis has important implications for developing a realistic, fact-based and truly equitable educational policy of long-range benefits to the nation as a whole. Due to limited resources, governments in many countries are forced to make difficult decisions about which levels of education-primary, secondary, or higher should be the recipients of scarce investment funds. To allocate these resources across levels of education, one could compare the costs and benefits of each of the three alternatives. The investment that yields the highest net benefits would produce relatively greater benefits for a given cost. Malaysia, like other countries in Southeast Asia, faces similar challenges in ensuring the allocation of appropriate funding for efficient and equitable educational services. This paper provides the conceptual framework for cost-benefit analysis on investment in primary, secondary and higher education in Malaysia. Distributional impact on different stakeholders has been analyzed by employing Kaldor-Hicks Tableau with the national accounting domain. Sensitivity analysis will be conducted using different discounting rates. This study also included the social benefits and costs in the conceptual framework to provide a comprehensive cost benefit analysis in Malaysian education system. Keywords: Educational policy, limited resources, investment funds, cost-benefit analysis.